Reference value of perimeter‐derived diameter assessed by three‐dimensional transesophageal echocardiography in left atrial appendage occluder size selection. Issue 11 (2nd October 2020) - Kong, Dehong; Jiang, Yingying; Zhang, Xiaochun; Jin, Qinchun; Dong, Lili; Zhou, Daxin; Shu, Xianhong; Pan, Cuizhen
Abstract: Background: The aim of this study was to investigate the utility of perimeter‐derived diameter (PDD) measured by three‐dimensional (3D) transesophageal echocardiography (TEE) in predicting the size of left atrial appendage (LAA) occluder. Methods and results: Left atrial appendage landing zone diameter (LZD) was measured by two‐dimensional (2D) TEE, 3DTEE, and digital subtraction angiography (DSA) as LZD‐2Dmax, LZD‐2Dmean, LZD‐3Dmax, LZD‐3Dmean, LZD‐PDD, LZD‐DSAmax, respectively, before and during transcatheter LAA closure with Watchman devices in 100 patients. A difference of one or more device size intervals between the predicted size and the size actually implanted was defined as mismatching. Seventy‐eight patients were followed up by TEE to obtain occluder compression ratio. The correlation between LZD and the final implanted occluder size was 0.559, 0.641, 0.754, 0.760, 0.782, and 0.848 for LZD‐2Dmax, LZD‐2Dmean, LZD‐3Dmax, LZD‐3Dmean, LZD‐PDD and LZD‐DSAmax, respectively ( P  < .001). Matching ratio between the size predicted by retrospective measurements of LZD and the device size actually implanted was 65%, 57%, 66%, 63%, 70%, and 83% for LZD‐2Dmax, LZD‐2Dmean, LZD‐3Dmax, LZD‐3Dmean, LZD‐PDD and LZD‐DSAmax, respectively. There was no significant difference in LZD value, matching ratio, and compression ratio between the patients with eccentric and noneccentric LAA landing zone ( P >  .05). Compression ratio of the mismatching subjects was higher than that in the matching subjects when evaluated by LZD‐2Dmean, LZD‐3Dmean, and LZD‐PDD ( P  < .05). Conclusions: Landing zone diameter derived from LAA perimeter measured by preprocedure 3DTEE showed reference value for LAA occluder size selection, providing superior correlation and matching ratio with the final implanted size and indicating the adjustment of oversizing.